2017
DOI: 10.1002/chem.201702890
|View full text |Cite
|
Sign up to set email alerts
|

2,6‐Bis(diazaboryl)pyridine: A Superbasic Sterically Demanding Pyridine Ligand.

Abstract: Herein a convenient one-pot route to a sterically demanding superbasic pyridine is presented. Functionalization of the 2- and 6-positions with the strongly σ-donating boryl-groups shifts the calculated gas phase basicity of the pyridine nitrogen atom to 1012 kJ mol , which outperforms the "proton sponge" 1,8-bis(dimethylamino)naphthalene (996 kJ mol ). The diazaboryl groups are oriented orthogonally to the pyridine ring and do not block the N-position, which resembles the geometry of commonly used N-heterocycl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
25
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 15 publications
(25 citation statements)
references
References 62 publications
(31 reference statements)
0
25
0
Order By: Relevance
“…When the analogous reaction of dab 2 py was conducted with GaCl 3 as the Lewis‐acid, no reaction was observed at room temperature, as monitored on a CD 2 Cl 2 solution by multinuclear NMR spectroscopy. This was unexpected, because dab 2 py readily forms a 1:1 adduct with BCl 3 , but GaCl 3 is the stronger Lewis‐acid (FIA [kJ/mol –1 ]: BCl 3 = 405; GaCl 3 = 432) . Neither did the ligand induced ionization process proceed, as observed for the analogous reaction of dab 2 py with AlBr 3 .…”
Section: Resultsmentioning
confidence: 95%
See 3 more Smart Citations
“…When the analogous reaction of dab 2 py was conducted with GaCl 3 as the Lewis‐acid, no reaction was observed at room temperature, as monitored on a CD 2 Cl 2 solution by multinuclear NMR spectroscopy. This was unexpected, because dab 2 py readily forms a 1:1 adduct with BCl 3 , but GaCl 3 is the stronger Lewis‐acid (FIA [kJ/mol –1 ]: BCl 3 = 405; GaCl 3 = 432) . Neither did the ligand induced ionization process proceed, as observed for the analogous reaction of dab 2 py with AlBr 3 .…”
Section: Resultsmentioning
confidence: 95%
“…Geometry optimization for the calculated 1:1 adduct dab 2 py→GaCl 3 clearly showed that the adduct formation is sterically hindered (TPSS‐D3(BJ)/def2‐TZVPP level of theory, see ESI). The gallium atom is displaced out of the pyridine plane with an angle between the N–Ga bond and the pyridine plane of 21.4° (the corresponding angle found in the crystal structure of dab 2 py→BCl 3 is only 6.0°) . The inability of the adduct formation of the Lewis‐base dab 2 py and the Lewis‐acid GaCl 3 due to steric hindrance is making this system by definition a Frustrated Lewis Pair (FLP)…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…On the other hand, the reactions carried out with n BuLi/TMEDA and t BuLi yielded Mes 2 Py; however, the reactions were not selective as Mes 2 Py was accompanied by significant amounts of byproducts, thereby rendering this route unfeasible. Recently, our group reported a one‐pot procedure for the borylation of pyridine at the 2,6‐postions by the addition of lithium to a solution of 2,6‐dibromopyridine and B(O i Pr) 3 . This protocol was adopted for the direct borylation of 2 ‐Cl.…”
Section: Resultsmentioning
confidence: 99%